Absolute Power is Sovereignty in the Philosophical Dimension - Yunus, Nur Rohim (ADALAH, 2024)
This essay examines the concept of sovereignty as the highest power in a state, focusing on the absolutist view that views sovereignty as the absolute power of the ruler. In a historical perspective, especially in medieval Europe, to the era of absolute monarchy, the highest power was considered to belong to the king, who was not limited by law or other institutions. Jean Bodin became an important figure who formulated sovereignty as the power that cannot be divided and comes from divine legitimacy. However, this view was challenged by liberal thinkers such as John Locke, who rejected absolute power and emphasised that true sovereignty lies in the hands of the people. He introduced the idea of limiting power through law and protecting fundamental individual rights, becoming the foundation of the modern legal state theory. In the current democratic system, sovereignty is manifested in the form of the supremacy of law, separation of powers, and popular participation. In the era of globalisation, the concept of absolute sovereignty is increasingly eroded. The state must submit to international law and agreements, showing that sovereignty is now limited and interrelated. This essay closes with a reflection on the fact that absolutism of power as sovereignty has evolved in the dynamics of the times.